The BLDC Simulation Study of Electronic Water Pump Based on MATLAB/Simulink - Liu, Xiaoping; Fan, Xiaobin; Wang, Feng; Zhao, Zixiang (Recent Patents on Mechanical Engineering, 2018)
Background: According to the characteristics of engine cooling system, a BLDC (Brushless direct current motor) modeling method based on the electronic water pump is proposed. In the MATLAB/ Simulink environment, according to the different functions of the motor body module, the driver module, and the control module, we can build each independent module, and then let them make an organic integration, so we can build the brushless direct current motor system simulation model based on the electronic water pump. We adopt the BLDC double closed-loop control system which is made up of the classic speed loop PI control and the current hysteresis control to ensure the rapid and effective response of the electronic water pump. Through the qualitative analysis of simulation analysis, this control method has better control effect for BLDC of electronic water pump, at the same time, the model can be applied to verify the rationality of other algorithms for BLDC control of electronic water pump, and provides a new idea for the research and debugging of BLDC motor for electronic water pump in the later period. Objective: This paper mainly focuses on the qualitative analysis of simulation, the model can be applied to verify the rationality of other algorithms for BLDC control of electronic water pump, and provides a new idea for the research and debugging of BLDC motor for electronic water pump in the later period. Methods: Firstly, according to the characteristics of engine cooling system, a BLDC modeling method based on the electronic water pump is proposed. Secondly, in the MATLAB/Simulink environment, according to the different functions of the motor body module, the driver module, and the control module, we can build each independent module, and then let them make an organic integration, so we can build the brushless direct current motor system simulation model based on the electronic water pump. Thirdly, we adopt the BLDC double closed-loop control system which is made up of the classic speed loop PI control and the current hysteresis control. Results: In the MATLAB/Simulink environment, according to the different functions of the motor body module, the driver module, and the control module, we can build each independent module, and then let them make an organic integration, so we can build the brushless direct current motor system simulation model based on the electronic water pump. Through the classical speed loop PI control and the current loop hysteresis control, the double closed loop control of the BLDC control system is formed. Conclusion: On the basis of analyzing the performance characteristics of the automobile electronic water pump, this paper puts forward the method of selecting the BLDC motor for the electric water pump, and designs the BLDC speed regulation system based on this, through the design of classical speed and current hysteresis control method, the model is simulated. The simulation results show that the waveform conforms to the theoretical analysis, and the system has better dynamic and static characteristics. Furthermore, on this basis, theoretical verification of various control algorithms for BLDC motors for electronic water pumps can be achieved, it can better realize the qualitative analysis of the BLDC working state of the electronic water pump. In this article, some patents have been discussed.
Keywords: Brushless direct current motor